2020
DOI: 10.1021/acs.jctc.0c00782
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Excited-State Proton Transfer to Solvent: A Dynamics Study of a Super Photoacid with a Hybrid Implicit/Explicit Solvent Model

Abstract: The rapid growth of time-resolved spectroscopies and the theoretical advances in ab initio molecular dynamics (AIMD) pave the way to look at the real-time molecular motion following the electronic excitation. Here, we exploited the capabilities of AIMD combined with a hybrid implicit/explicit model of solvation to investigate the ultrafast excited-state proton transfer (ESPT) reaction of a super photoacid, known as QCy9, in water solution. QCy9 transfers a proton to a water solvent molecule within 100 fs upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 51 publications
0
40
0
Order By: Relevance
“…In a recent work, we explored the ESPT reaction of a superphotoacid to the solvent by means of the same QM/MM hybrid scheme. 86 Despite the ultrafast reactivity (100 fs), we found that the ESPT is assisted by the solvation dynamics of the water molecules belonging to the first and second solvation shell of the first accepting water molecule. Additionally, we found that this event can be reproduced only when solvation shells around the proton are taken into account at the full QM level.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…In a recent work, we explored the ESPT reaction of a superphotoacid to the solvent by means of the same QM/MM hybrid scheme. 86 Despite the ultrafast reactivity (100 fs), we found that the ESPT is assisted by the solvation dynamics of the water molecules belonging to the first and second solvation shell of the first accepting water molecule. Additionally, we found that this event can be reproduced only when solvation shells around the proton are taken into account at the full QM level.…”
Section: Resultsmentioning
confidence: 78%
“… 30 , 35 The ESPT kinetics is however strongly dependent on the nuclear structure of the starting configuration, i.e., the intermolecular distances of the proton donor–acceptor pair and their relative orientation, in addition to the solvation around the reactive core. 3 , 4 , 86 If the starting nuclear configuration is structurally prepared for the ESPT reaction, it reasonable to expect an ESPT in the subpicosecond time scale.…”
Section: Resultsmentioning
confidence: 99%
“…the bulk solvent, when molecularity is less important, will probably represent a significant advance in this field. Since QM/MM methods with localised basis sets are more straightforwardly applied without periodic boundary conditions, non-periodic approaches, like the generalized liquid optimized boundary (GLOB) model, 44,221,222 will probably play an important role. Recent attempts to combine GLOB ideas with the use of polarizable FFs look very promising.…”
Section: Discussionmentioning
confidence: 99%
“…117 For short time-scales a wise increase of the QM subset to include some solvent molecules is an option, at least in the case of well-defined specific solute-solvent interactions. 44 On the other hand, the number of discrete QM solvent molecules necessary to simulate bulk properties is a currently open question, even for static properties. 216,224 In terms of the dynamics methods to be combined with explicit solvent approaches, at-the-state of the art the most popular and widely used are those that propagate all nuclear degrees of freedom with classical dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Although implicit solvent models, such as the polarizable continuum models, [18][19][20][21][22][23][24] are now widely available in QC packages and the corresponding molecular property data set curation can be easily automated with the aforementioned QC workflows, the accuracy of these calculations cannot always meet our needs in design and discovery. Accurate prediction of many molecular properties requires QC calculation in explicit solvents due to the existence of proton transfer, 25,26 hydrogen bonds, [27][28][29] or other strong solute-solvent interactions. Setting up QC calculations of explicitly solvated molecules usually involves multiple steps, including building the structure of the solute molecule in a solvent box, generating a customized force field for solute/solvent, running molecular dynamics (MD) simulations at molecular mechanical (MM) and hybrid quantum mechanical and molecular mechanical (QM/MM) [30][31][32][33][34] level of theories to obtain equilibrated solvation configurations, and the final QC calculation of molecular properties for the microsolvated molecule extracted from the solvent box.…”
Section: Introductionmentioning
confidence: 99%